Adrenal histoplasmosis : a rare cause of bilateral adrenomegaly - Subedi, PP; Chapagain, S; Thakur, DK; Poudyal, S; Luitel, BR; Chalise, PR; Sharma, UK; Gyawali, PR; Shrestha, GK (Journal of Society of Surgeons of Nepal, 2016)
Histoplasmosis is an opportunistic infection caused by a dimorphic fungus Histoplasma capsulatum. Histoplasmosis causing bilateral adrenal involvement is rare and usually occurs only in immunocompromised individuals with disseminated disease. Here we report a case of bilateral adrenal histoplasmosis with disseminated disease in an immunocompetent patient.